KORELASI KUALITAS AIR DENGAN PREVALENSI EKTOPARASIT PROTOZOA PADA IKAN GABUS (Channa striata) SEBAGAI KANDIDAT DOMESTIKASI YANG TERTANGKAP DI PERAIRAN RAWA GAMBUT DESA TANJUNG TARUNA - Suraya, Ummi; Oktavia, Wiwin; Rosita; Maryani (JOURNAL OF TROPICAL FISHERIES, 2025)
The study aimed at determine of the type, amount, prevalence of Ectoparasite Protozoan, water quality,, and correlation of Water Quality Against Prevalence of Ectoparasite Protozoan in Snakehead Fish (Channa striata) As Domestic Candidates Caught in Peat Swamp Waters. The method used in this research are descriptive analysis method and correlation test. This research is done during December 2022 in Peat Swamp Waters in Tanjung Taruna, Tanjung Taruna Village, Jabiren Raya District, Pulang Pisau Regency, Central Kalimantan Province and examination of ectoparasite protozoan at the Parasitology Laboratory Station, Fish Quarantine Quality Control and Safety of Fishery Products Palangka Raya. Measurements of water quality were carried out in situ at each fishing coordinate point for 4 times sampling, wuth an interval of one week during a month of research. Based on the measurement result of water quality parameters indicate that the temperature ranges between 28,1-29,2oC, brightness 25-39,5 cm, pH 4,55-6,2, dissolved oxygen 3,3-4,7, nitrite 0,02-0,03 mg/L, and nitrate 0,4-0,6 mg/L. The result of prevalence ectoparasite protozoan was 96,67% with individu prevalence highest of vorticella sp ectoparasite protozoan were 51,67% and lowest were 23,33% at Epistylis sp ectoparasite protozoan. There is a strong correlation between temperature and total dissolved solid with total prevalence ectoparasite protozoan, brightness and nitrite have very low correlation with total prevalence ectoparasite protozoan, pH and DO have very strong correlation with total prevalence ectoparasite protozoan, and nitrate no correlation with total prevalence ectoparasite protozoan.